A novel case of left atrial and right lung mass turned out to be unconventional metastasis of uterine leiomyosarcoma with a review of literature - Tarang Patel; Priyanka Aswal; Ashish Jakhetiya; Virendrakumar Meena; Arun Pandey (Indian Journal of Pathology and Microbiology)
Uterine leiomyosarcoma (ULMS) is a rare malignancy arising from the myometrial smooth muscle wall, and cardiac metastases are extremely rare. Metastasis to the heart is a very unusual finding, and atrial metastasis is even rarer. Here, we report a case of a 45 year old woman who presented with dyspnea and pleural effusion and had a significant history of hysterectomy done for ULMS. Magnetic resonance imaging revealed a left atrial mass, which was resected and revealed to be a metastasis of leiomyosarcoma on histopathology and immunohistochemistry. Metastatic ULMS may rarely present as a left atrial mass with acute clinical presentation. Detailed clinical history and accurate diagnosis are vital for further management.